Deviant globalization: the application of strategic landpower*. Issue 4 (1st October 2016) - Hillison, Joel R.; Isaacson, Avram
ABSTRACT: In both Afghanistan and Iraq, US landpower was able to gain control rapidly over terrain. However, that control ebbed as US presence weakened. Non-state actors, such as the Taliban, the Haqqani network, the Islamic State, and Al Qaeda, gained control of segments of the population. Transnational Criminal Organizations capitalized on this permissive environment to strengthen their networks, often eroding the legitimacy of the host nation government, fueling regional instability, and, ultimately, undermining US policy objectives. The proliferation of deviant globalization, or the connectedness of subversive elements, is a key indicator of future conflict. Strategic landpower is uniquely positioned to influence the physical, psychological, economic, and social interactions of various non-state actors and their association with deviant globalization. It is no longer enough to seize and hold terrain. Landpower must also have the capability to influence the actions and attitudes of populations on that terrain wherever and whenever these interactions occur.